Panel building refurbishment elements effective selection by applying multiple-criteria methods - Kracka, Modestas; Zavadskas, Edmundas Kazimieras (International Journal of Strategic Property Management, 2013)
Sustainable development has taken on a new concept: building maintenance, materials production, buildings demolition to determine the amount of energy and resources. This paper presents the process of effective selection of building elements for renovation which are important for energy effectiveness of buildings. Multi-criteria MOORA and MULTIMOORA methods has been adapt for problems solving with interval data. The paper presents a theoretical model of practice design renovation solutions evaluated. The theoretical model can also be applied to practical solutions to assess new construction planning stage, and other life-building processes. First Publish Online: 27 Jun 2013